An evaluation of the Sennheiser HDA 280-CL circumaural headphone for use in audiometric testing. (3rd July 2019) - Folkeard, Paula; Hawkins, Marianne; Scollie, Susan; Sheikh, Bilal; Parsa, Vijay
Abstract: Objective: Evaluation of the Sennheiser HDA 280-CL circumaural headphone for the determination of (1) equivalent threshold sound pressure levels (ETSPL) for 125–18, 000 Hz.; (2) real ear attenuation (250–8000 Hz); (3) insertion loss (63–18, 000 Hz); (4) frequency response (125–18, 000 Hz); (5) total harmonic distortion (THD) (125–10, 000 Hz); and, (6) linearity (11, 200–18, 000 Hz).Study Sample: Twenty-five normal hearing adults aged 18–25 participated in (1) and (2).Design: (1) Hearing thresholds were measured using the Sennheiser HDA 280-CL. Frequency specific ETSPL values were calculated in an artificial ear. (2) Sound field thresholds were measured with the ears open and covered with the headphone to obtain the real ear attenuation thresholds (REAT). These values were used to determine the maximum permissible ambient noise levels (MPANL). (3) A B&K HATS mannequin recorded the output levels of a broadband pink noise with the ears open and covered with the headphones. (4, 5) The frequency response, THD and linearity were measured in an artificial ear.Results: Values for ETSPL, REAT, MPANL, insertion loss, as well as measures of frequency response, THD and linearity are presented.Conclusions: The Sennheiser HDA 280-CL meets the requirements for audiometric testing and the values presented can be used for calibration.